2021
DOI: 10.1038/s41598-021-99104-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome signature and diversity regulates the level of energy production under anaerobic condition

Abstract: The microbiome of the anaerobic digester (AD) regulates the level of energy production. To assess the microbiome diversity and composition in different stages of anaerobic digestion, we collected 16 samples from the AD of cow dung (CD) origin. The samples were categorized into four groups (Group-I, Group-II, Group-III and Group-IV) based on the level of energy production (CH4%), and sequenced through whole metagenome sequencing (WMS). Group-I (n = 2) belonged to initial time of energy production whereas Group-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…The relationships between the soil dominant environmental factors (Ca 2+ , AP, EC e , AK and urease) and the soil microbial community were analyzed by using redundancy analysis (RDA). The correlations between the basic soil physical and chemical properties and the specific bacterial and fungal phyla relative abundances were analyzed by using Spearman’s analyses in the ggcorrplot package in R (version 3.6.2) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The relationships between the soil dominant environmental factors (Ca 2+ , AP, EC e , AK and urease) and the soil microbial community were analyzed by using redundancy analysis (RDA). The correlations between the basic soil physical and chemical properties and the specific bacterial and fungal phyla relative abundances were analyzed by using Spearman’s analyses in the ggcorrplot package in R (version 3.6.2) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different species of Saccharomycetales such as S. paradoxus, S. kudriavzevii, K. lactis, K. aquatica, Y. lipolytica had an opportunistic inclusion in COVID-19 patients (Fig 9, S1 Data). Earlier evidences suggested that different species Saccharomycetales can only perform opportunistic or passive crossings when epithelial barrier integrity of the NT is previously compromised by other infectious agents [70]. For instance, S. kudriavzevii an opportunistic pathogen especially potential hazard to the health of immunocompromised workers in the wine industry, and potentially also to consumers [61].…”
Section: Discussionmentioning
confidence: 99%
“…alignment length cut off: 20) [69]. The association between metabolic functions and dominant fungal species were measured using the Spearman’s correlation coefficient and significance tests [70]. The R packages, Hmisc (https://cran.r-project.org/web/packages/Hmisc/index.html) and corrplot (https://cran.r-project.org/web/packages/corrplot/vignettes/corrplot-intro.html) were used respectively to analyze and visualize the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-trivial, timeconsuming and costly nature of microbial analysis (i.e., meta-omics techniques) is arguably a contributing factor to the paucity of microbial characterisation in the field, although the cost and complexity of genetic sequencing has dropped sharply since the early 2000s with the emergence of next-generation sequencing [63]. Nevertheless, the ability to link taxonomic data with functional insights remains limited [64], which is need before a comprehensive picture of metabolic pathways occurring within a given AD system can be drawn. Strengthening public-private partnerships could accelerate knowledge transfer to and put research into practice.…”
Section: Microbial Communitiesmentioning
confidence: 99%